Pemberdayaan Usaha Mikro Kecil (UMK) Mahasiswa melalui pengembangan dan produksi Varian Formulasi Produk Sajag - Budijono Budijono; Yudho Harjoyudanto; Rina D’rita Sibagariang; Muhammad Fauzi; Eko Prianto; Windarti Windarti; Eddiwan Eddiwan; Yuliati Yuliati; Isma Mulyani; Romie Jhonnerie (CANANG: Jurnal Pengabdian Masyarakat, 2023)
The findings of research products that have the potential to become entrepreneurial products are SAJAG (magic powder for peat water purification) with variant formulations of CaO+PAC and CaO+Al2(SO4)3+PAC ingredients that have not been produced and patented in the same packaging and brand. The objectives of this service are to: (1) transfer the results of science and technology directly to UMK partners, students/alumni of the University of Riau through the development and production of variants of SAJAG material formulations; (2) fostering the entrepreneurial spirit of students with SAJAG products; (3) produce useful and economically valuable products from research results that have the potential to be marketed by UMK students as entrepreneurial actors; (4) generate student income potential from marketing SAJAG products. The methods of counseling, training and independent practice as well as mentoring are used in implementing the activities to 25 students/alumni who are members of business partners. From the results of this activity, knowledge changes in the target community groups have been obtained and have succeeded in implementing skills by producing a total of 7000 sachets of product for 10L volume of peat water, of which 1500 sachets were successfully sold with a sales value of Rp. 3,750,000. The production process continued until simple patents were obtained for the two variants of SAJAG products to be marketed, managed by the 'BAHARI' group as a new student business partner.